The composition and friction-reducing properties of leaf layers. (29th July 2020) - Watson, Michael; White, Benjamin; Lanigan, Joseph; Slatter, Tom; Lewis, Roger
Abstract : Every autumn rail networks across the world suffer delays, accidents and schedule changes due to low friction problems caused by leaves landing on the rails. These leaves form a layer that can reduce the friction between the wheel and the rail to a similar level as that between ice and an ice-skate (μ = 0.01 – 0.05 ). Previous works have generated several hypotheses for the chemical reactions and low friction mechanism associated with these layers. In this work, the reaction between an aqueous extract of sycamore leaves and metallic iron is investigated. This reaction has been shown to produce a black precipitate, which matches field observations of leaf layers, while friction tests with these extracts produce characteristic ultra low friction. The reaction is investigated through FTIR, XPS, CHNS and ICP-MS analysis as well as wet chemical testing. The impact of the reaction on friction is investigated through three rounds of tribological testing. The results indicate that the black precipitate produced is iron tannate, formed by complexation of tannins with dissolved iron ions. Friction testing showed that eliminating tannins from the leaf extract resulted in a significant increase in the friction coefficient compared with the control.